5-HT7 receptors as a new target for prostate cancer physiopathology and treatment: an experimental study on PC-3 cells and FFPE tissues - Cinar, Irfan; Sirin, Busra; Halici, Zekai; Palabiyik-Yucelik, Saziye Sezin; Akpinar, Erol; Cadirci, Elif (Springer Science and Business Media LLC, 2021)
Prostate cancer (PCa) is one of the most common types of cancer seen among men worldwide. Previous studies have demonstrated that serotonin regulates cell proliferation, migration, and invasion in vitro; the presence of 5-HT receptors in cancer cells; and the role of serotonin in tumor development. The most recently discovered of these receptors is 5-HT7 but also least characterized receptors of serotonin. The aim of this study is to investigate the existence and possible role of 5-HT7 receptors in healthy and cancerous prostate tissues and also investigate effects of receptor agonists and antagonists on PC-3 cells to evaluate potential therapeutic effects. PC-3 cells were cultured and effects of 5-HT7 receptor agonist (LP-44) and antagonist (SB-269970) were evaluated on these cells. After proliferation analyses, relative expression of apoptotic markers and 5-HT7 receptor mRNA expression levels were determined through real-time PCR. Annexin V-FITC/PI double staining and Hoechst 33258 staining assay methods were applied to determine apoptosis. Additional PCR studies were performed on healthy and cancerous prostate tissue to see existence of receptors in human samples. The viability of PC-3 cells was decreased by SB-269970 after 48 and 72 h of incubation. However, LP-44 increased PC-3 cell proliferation at all time points. In 10-6 M SB-269970 treated PC-3 cells, there was significant increase in the expression of CAS-3 (4-fold), CAS-9 (2.5-fold), BAX (1.9-fold), and Tp-53 (4.8-fold) gene mRNA levels when compared to non-treated control group. Conversely, there was a significant decrease in NF-κB (2.9-fold) and 5-HT7 receptor (3.6-fold) mRNA expression in cells treated with SB-269970 when compared to control. SB-269970 that antagonized 5-HT7 receptors also induced apoptosis in Annexin V-FITC/PI double staining assay and Hoechst 33258 staining assays when compared with other groups. In human samples, 5-HT7 receptor mRNA expression was approximately 200-fold higher than that of heathy ones. In this study, for the first time, the 5-HT7 receptor antagonist SB-269970 has been shown to inhibit proliferation in PC-3 cells and to be associated with an apoptosis-inducing effect. These results suggest blocking 5-HT7 receptors can be a novel therapeutic target for the treatment of prostate cancer.
Keywords: Male; Sulfonamides; Time Factors; Tetrahydronaphthalenes; Prostatic Neoplasms; Apoptosis; Piperazines; Serotonin Receptor Agonists; Gene Expression Regulation, Neoplastic; Phenols; Receptors, Serotonin; PC-3 Cells; Humans; RNA, Messenger; Serotonin Antagonists; Cell Proliferation; 3. Good health